Application of Compressive Sensing to Gravitational Microlensing Experiments. Issue Volume 12:Issue S325(2016) (30th May 2017) - Korde-Patel, Asmita; Barry, Richard K.; Mohsenin, Tinoosh
Abstract: Compressive Sensing is an emerging technology for data compression and simultaneous data acquisition. This is an enabling technique for significant reduction in data bandwidth, and transmission power and hence, can greatly benefit space-flight instruments. We apply this process to detect exoplanets via gravitational microlensing. We experiment with various impact parameters that describe microlensing curves to determine the effectiveness and uncertainty caused by Compressive Sensing. Finally, we describe implications for space-flight missions.